Roadmap on electromagnetic metamaterials and metasurfaces - Cui, Tie Jun; Zhang, Shuang; Alu, Andrea; Wegener, Martin; Pendry, John; Luo, Jie; Lai, Yun; Wang, Zuojia; Lin, Xiao; Chen, Hongsheng; Chen, Ping; Wu, Rui-Xin; et al. (Journal of Physics: Photonics)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

An alternative and robust formulation of the fatigue crack growth rate curve for long cracks - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Multiscale simulation of polymer curing of composites combined mean-field homogenisation methods at large strains - Lenz, Peter; Mahnken, Rolf (International Journal of Solids and Structures)
Keywords: Applied Mathematics; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science; Modeling and Simulation

Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Dynamics of Electron–Hole Coulomb Attractive Energy and Dipole Moment of Hot Excitons in Donor–Acceptor Polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Influences of Weld Nugget Shape and Material Gradient on the Shear Strength of Resistance Spot‐Welded Joints - Schuster, Lilia; Olfert, Viktoria; Sherepenko, Oleksii; Fehrenbach, Clemens; Song, Shiyuan; Hein, David; Meschut, Gerson; Biro, Elliot; Münstermann, Sebastian (steel research international)
Resistance spot‐welded joints containing press‐hardened steels are seen to exhibit a fracture mode called total dome failure, where the weld nugget completely separates from one steel sheet along the weld nugget edge. The effect of weld nugget shape and material property gradients is studied based on damage mechanics modeling and experimental validation to shed light on the underlying influencing factors. For a three‐steel‐sheet spot‐welded joint combining DP600 (1.5 mm)–CR1900T (1.0 mm)–CR1900T (1.0 mm), experiments under shear loading reveal that fracture occurs in the DP600 sheet along the weld nugget edge. In subsequent numerical simulation studies with damage mechanics models whose parameters are independently calibrated for every involved material configuration, three variations of the geometrical joint configuration are considered—an approximation of the real joint, one variation with a steeper weld nugget shape, and one variation with a less pronounced gradient between weld nugget material and heat‐affected zone material properties. The results of the finite‐element simulations show that a shallower weld nugget and a more pronounced material gradient lead to a faster increase of plastic strain at the edge of the weld nugget and promote the occurrence of total dome failure.
Keywords: Materials Chemistry; Metals and Alloys; Physical and Theoretical Chemistry; Condensed Matter Physics

Anisotropic Mechanical and Microstructural Properties of a Ti-6Al-7Nb Alloy for Biomedical Applications Manufactured via Laser Powder Bed Fusion - Milaege, Dennis; Eschemann, Niklas; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
Through tailoring the geometry and design of biomaterials, additive manufacturing is revolutionizing the production of metallic patient-specific implants, e.g., the Ti-6Al-7Nb alloy. Unfortunately, studies investigating this alloy showed that additively produced samples exhibit anisotropic microstructures. This anisotropy compromises the mechanical properties and complicates the loading state in the implant. Moreover, the minimum requirements as specified per designated standards such as ISO 5832-11 are not met. The remedy to this problem is performing a conventional heat treatment. As this route requires energy, infrastructure, labor, and expertise, which in turn mean time and money, many of the additive manufacturing benefits are negated. Thus, the goal of this work was to achieve better isotropy by applying only adapted additive manufacturing process parameters, specifically focusing on the build orientations. In this work, samples orientated in 90°, 45°, and 0° directions relative to the building platform were manufactured and tested. These tests included mechanical (tensile and fatigue tests) as well as microstructural analyses (SEM and EBSD). Subsequently, the results of these tests such as fractography were correlated with the acquired mechanical properties. These showed that 90°-aligned samples performed best under fatigue load and that all requirements specified by the standard regarding monotonic load were met.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Electrochemical Removal of HF from Carbonate-based LiPF6-containing Li-ion Battery Electrolytes - Ge, Xiaokun; Huck, Marten; Kuhlmann, Andreas; Tiemann, Michael; Weinberger, Christian; Xu, Xiaodan; Zhao, Zhenyu; Steinrueck, Hans-Georg (Journal of The Electrochemical Society)
Due to the hydrolytic instability of LiPF6 in carbonate-based solvents, HF is a typical impurity in Li-ion battery electrolytes. HF significantly influences the performance of Li-ion batteries, for example by impacting the formation of the solid electrolyte interphase at the anode and by affecting transition metal dissolution at the cathode. Additionally, HF complicates studying fundamental interfacial electrochemistry of Li-ion battery electrolytes, such as direct anion reduction, because it is electrocatalytically relatively unstable, resulting in LiF passivation layers. Methods to selectively remove ppm levels of HF from LiPF6-containing carbonate-based electrolytes are limited. We introduce and benchmark a simple yet efficient electrochemical in situ method to selectively remove ppm amounts of HF from LiPF6-containing carbonate-based electrolytes. The basic idea is the application of a suitable potential to a high surface-area metallic electrode upon which only HF reacts (electrocatalytically) while all other electrolyte components are unaffected under the respective conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Cold denaturation of DNA origami nanostructures - Dornbusch, Daniel; Hanke, Marcel; Tomm, Emilia; Kielar, Charlotte; Grundmeier, Guido; Keller, Adrian; Fahmy, Karim (Chemical Communications)
The coupling of structural transitions to heat capacity changes leads to destabilization of macromolecules at both, elevated and lowered temperatures. DNA origami not only exhibit this property but also provide...
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Frustrated Lewis Pair Catalysed Reactions - Zhou, Rundong; Tavandashti, Zoleykha; Paradies, Jan (SynOpen)
In recent years, frustrated Lewis pairs have been widely used in small molecules activation and catalytic transformations. This graphic review is aimed to provide the fundamental understanding of frustrated Lewis pair reactivity and the exploitation thereof in catalytic reactions.
Keywords: Organic Chemistry; Materials Science (miscellaneous); Biomaterials; Catalysis

Nonlinear Dielectric Nanoresonators and Metasurfaces: Toward Efficient Generation of Entangled Photons - Sharapova, Polina R.; Kruk, Sergey S.; Solntsev, Alexander S. (Laser & Photonics Reviews)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Development of a numerical simulation model for self-piercing riveting of additive manufactured AlSi10Mg - Heyser, Per; Petker, Rudolf; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Laser additive manufacturing processes are used for the production of highly complex geometric structures due to their high geometric freedom. Additive manufacturing processes, in particular powder-based selective laser melting, are used to produce metallic additive manufactured components for the automotive and aerospace industries. Different materials are often joined together to realize sustainable lightweight construction. The production of such mixed construction joints is often realized using mechanical joining technology (e.g. self-piercing riveting). However, there is currently very little experience with the mechanical joining of metallic additive manufacturing components. Furthermore, there is insufficient knowledge about the effects that occur during the mechanical joining of additive manufacturing components. In this article, a method is presented to investigate the joinability of additively manufactured components with conventionally manufactured components using a numerical simulation of the self-piercing riveting process. For this purpose, the additive manufacturing materials are characterized experimentally, the simulation model is configured, and the joining process with additive manufacturing materials is represented in the numerical simulation. Furthermore, the influence of the building direction on the mechanical properties is shown using miniature tensile specimens. Besides the configuration of the simulation model, the influence of heat treatment on the self-piercing riveting process is presented.
Keywords: Mechanical Engineering; General Materials Science

Characterizing Ion Transport in Electrolytes via Concentration and Velocity Profiles - Mistry, Aashutosh; Srinivasan, Venkat; Steinrück, Hans-Georg (Advanced Energy Materials)
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment

Correction: Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koshukow, Wikentij; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Application of a new strategy for time-efficient laser treatment of galvanized steel substrates to improve the adhesion properties - Voswinkel, Dietrich (Journal of Manufacturing Processes)
Laser structuring to improve the adhesion properties of steel substrates in fiber-metal laminates offers many advantages that are highly suitable for modern industrial requirements. Maintenance and energy costs are relatively low, it is easy to automate, and there are no by-products such as chemicals or abrasives to dispose of or recycle. This makes laser structuring a particularly environmentally friendly process, which is nowadays more important than ever. On the other hand, the process time for laser structuring is much higher than for chemical pre-treatment, for example. In past studies, the time and cost efficiency of the laser structuring process has tended to play a minor role. However, there are approaches in which laser structured surfaces are adapted to the shear stress peaks occurring within the adhesive layer, thus requiring only partial structuring of the area to be bonded, potentially saving process time. In this experimental study, electrolytically galvanized steel substrates were partially laser structured to match the shear stress distribution and then bonded to a carbon fiber-reinforced plastic. The adhesion properties achieved were characterized using shear tensile tests and compared with the properties of the fully structured ones. With the partial laser structuring, a saving of 66 % of the conventional process time was achieved while maintaining 95 % of the same shear strength.
Keywords: Laser treatment Adhesive bonding Surface technology Hybrid materials

Realization of a Multi-Output Quantum Pulse Gate for Decoding High-Dimensional Temporal Modes of Single-Photon States - Serino, Laura; Gil López, Jano; Stefszky, Michael; Ricken, Raimund; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (PRX Quantum)
Keywords: General Physics and Astronomy; Mathematical Physics; Applied Mathematics; Electronic; Optical and Magnetic Materials; Electrical and Electronic Engineering; General Computer Science

Morphological and mechanical properties of foamed thick-walled Wood-Plastic-Composite structures - Moritzer, Elmar; Flachmann, Felix (Journal of Cellular Plastics)
Microcellular wood fiber reinforced polymers offer the possibility to reduce the use of fossil raw materials. In particular, thick-walled structures with thicknesses greater than 6 mm offer a high potential for weight savings. This study investigates the cell structures and mechanical properties of injection-molded test specimens. The influence of different thicknesses (6–10 mm) along with different chemical blowing agents (endothermic, exothermic) with varying dosages (0–2 wt%) is analyzed. The investigations reveal that exothermic chemical blowing agents form finer cells consistently to thin-walled structures than endothermic ones. Higher foaming agent content leads to higher pore fractions, with many small cells coalescing into a large open-pore cell network. The mechanical properties depend mainly on the pore content of the sample. The specific tensile properties deteriorate with the use of chemical blowing agents (CFA), whereas the sandwich structure produced with compact edge layers has a positive influence on the specific flexural properties.
Keywords: Materials Chemistry; Polymers and Plastics; General Chemistry

Development of an adaptive coaxial concrete rheometer and rheological characterisation of fresh concrete - Josch, Sebastian; Jesinghausen, Steffen; Schmid, Hans-Joachim (Applied Rheology)
Abstract The accessibility to rheological parameters for concrete is becoming more and more relevant. This is mainly related to the constantly emerging challenges, such as not only the development of high-strength concretes is progressing very fast but also the simulation of the flow behaviour is of high importance. The main problem, however, is that the rheological characterisation of fresh concrete is not possible via commercial rheometers. The so-called concrete rheometers provide valuable relative values for comparing different concretes, but they cannot measure absolute values. Therefore, we developed an adaptive coaxial concrete rheometer (ACCR) that allows the measurement of fresh concrete with particles up to d max = 5.5 mm {d}_{{\rm{\max }}}=5.5\hspace{.5em}{\rm{mm}} . The comparison of the ACCR with a commercial rheometer showed very good agreement for selected test materials (Newtonian fluid, shear thinning fluid, suspension, and yield stress fluid), so that self-compacting concrete was subsequently measured. Since these measurements showed a very high reproducibility, the rheological properties of the fresh concrete could be determined with high accuracy. The common flow models (Bingham (B), Herschel–Bulkley, modified Bingham (MB) models) were also tested for their applicability, with the Bingham and the modified Bingham model proving to be the best suitable ones.
Keywords: Condensed Matter Physics; General Materials Science

Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koschukow, Wikentji; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Understanding the Redox Mechanism of Sulfurized Poly(acrylonitrile) as Highly Rate and Cycle Stable Cathode Material for Sodium-Sulfur Batteries - Kappler, Julian; Tonbul, Güldeniz; Schoch, Roland; Murugan, Saravanakumar; Nowakowski, Michał; Lange, Pia Lena; Klostermann, Sina Vanessa; Bauer, Matthias; Schleid, Thomas; Kästner, Johannes; Buchmeiser, Michael Rudolf (Journal of The Electrochemical Society)
Room temperature sodium-sulfur (RT Na-S) batteries are considered potential candidates for stationary power storage applications due to their low cost, broad active material availability and low toxicity. Challenges, such as high volume expansion of the S-cathode upon discharge, low electronic conductivity of S as active material and herewith limited rate capability as well as the shuttling of polysulfides (PSs) as intermediates often impede the cycle stability and practical application of Na-S batteries. Sulfurized poly(acrylonitrile) (SPAN) inherently inhibits the shuttling of PSs and shows compatibility with carbonate-based electrolytes, however, its exact redox mechanism remained unclear to date. Herein, we implement a commercially available and simple electrolyte into the Na-SPAN cell chemistry and demonstrate its high rate and cycle stability. Through the application of in situ techniques utilizing electronic impedance spectroscopy (EIS) and X-ray absorption spectroscopy (XAS) at different depths of charge and discharge, an insight into SPAN’s redox chemistry is obtained.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Large-Scale Formation of DNA Origami Lattices on Silicon - Tapio, Kosti; Kielar, Charlotte; Parikka, Johannes M.; Keller, Adrian; Järvinen, Heini; Fahmy, Karim; Toppari, J. Jussi (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Stability of DNA Origami Nanostructures in Physiological Media: The Role of Molecular Interactions - Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Compact Metasurface-Based Optical Pulse-Shaping Device - Geromel, René; Georgi, Philip; Protte, Maximilian; Lei, Shiwei; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
Dispersion is present in every optical setup and is often an undesired effect, especially in nonlinear-optical experiments where ultrashort laser pulses are needed. Typically, bulky pulse compressors consisting of gratings or prisms are used to address this issue by precompensating the dispersion of the optical components. However, these devices are only able to compensate for a part of the dispersion (second-order dispersion). Here, we present a compact pulse-shaping device that uses plasmonic metasurfaces to apply an arbitrarily designed spectral phase delay allowing for a full dispersion control. Furthermore, with specific phase encodings, this device can be used to temporally reshape the incident laser pulses into more complex pulse forms such as a double pulse. We verify the performance of our device by using an SHG-FROG measurement setup together with a retrieval algorithm to extract the dispersion that our device applies to an incident laser pulse.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Comparative Study of the Influence of Heat Treatment and Additive Manufacturing Process (LMD & L-PBF) on the Mechanical Properties of Specimens Manufactured from 1.2709 - Gnaase, Stefan; Niggemeyer, Dennis; Lehnert, Dennis; Bödger, Christian; Tröster, Thomas (Crystals)
(1) This work answers the question of whether and to what extent there is a significant difference in mechanical properties when different additive manufacturing processes are applied to the material 1.2709. The Laser-Powder-Bed-Fusion (L-PBF) and Laser-Metal-Deposition (LMD) processes are considered, as they differ fundamentally in the way a part is manufactured. (2) Known process parameters for low-porosity parts were used to fabricate tensile strength specimens. Half of the specimens were heat-treated, and all specimens were tested for mechanical properties in a quasi-static tensile test. In addition, the material hardness was determined. (3) It was found that, firstly, heat treatment resulted in a sharp increase in mechanical properties such as hardness, elastic modulus, yield strength and ultimate strength. In addition to the increase in these properties, the elongation at break also decreases significantly after heat treatment. The choice of process, on the other hand, does not give either process a clear advantage in terms of mechanical properties but shows that it is necessary to consider the essential mechanical properties for a desired application.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

A Pulsed Lidar System With Ultimate Quantum Range Accuracy - Kruse, Stephan; Serino, Laura; Folge, Patrick Fabian; Echeverria Oviedo, Dana; Bhattacharjee, Abhinandan; Stefszky, Michael; Scheytt, J. Christoph; Brecht, Benjamin; Silberhorn, Christine (IEEE Photonics Technology Letters)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Integrating Prospective LCA in the Development of Automotive Components - Grenz, Julian; Ostermann, Moritz; Käsewieter, Karoline; Cerdas, Felipe; Marten, Thorsten; Herrmann, Christoph; Tröster, Thomas (Sustainability)
The development of automotive components with reduced greenhouse gas (GHG) emissions is needed to reduce overall vehicle emissions. Life Cycle Engineering (LCE) based on Life Cycle Assessment (LCA) supports this by providing holistic information and improvement potentials regarding eco-efficient products. Key factors influencing LCAs of automotive components, such as material production, will change in the future. First approaches for integrating future scenarios for these key factors into LCE already exist, but they only consider a limited number of parameters and scenarios. This work aims to develop a method that can be practically applied in the industry for integrating prospective LCAs (pLCA) into the LCE of automotive components, considering relevant parameters and consistent scenarios. Therefore, pLCA methods are further developed to investigate the influence of future scenarios on the GHG emissions of automotive components. The practical application is demonstrated for a vehicle component with different design options. This paper shows that different development paths of the foreground and background system can shift the ecological optimum of design alternatives. Therefore, future pathways of relevant parameters must be considered comprehensively to reduce GHG emissions of future vehicles. This work contributes to the methodological and practical integration of pLCA into automotive development processes and provides quantitative results.
Keywords: prospective LCA; life cycle engineering (LCE); lightweight design; automotive components; body parts; circular economy; steel; aluminum; hybrid materials; fiber metal laminates

Engineering Sub‐Nanometer Hafnia‐Based Ferroelectric to Break The Scaling Relation for High‐Efficiency Piezocatalytic Water Splitting - Su, Ran; Zhang, Jiahui; Wong, Vienna; Zhang, Dawei; Yang, Yong; Luo, Zheng‐Dong; Wang, Xiaojing; Wen, Hui; Liu, Yang; Seidel, Jan; Yang, Xiaolong; Pan, Ying; et al. (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Cation-dependent assembly of hexagonal DNA origami lattices on SiO2 surfaces - Pothineni, Bhanu Kiran; Grundmeier, Guido; Keller, Adrian (Nanoscale)
DNA origami nanostructures have emerged as functional materials for applications in various areas of science and technology. In particular, the transfer of the DNA origami shape into inorganic materials using...
Keywords: General Materials Science

Remote Epitaxy of Cubic Gallium Nitride on Graphene‐Covered 3C‐SiC Substrates by Plasma‐Assisted Molecular Beam Epitaxy - Littmann, Mario; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Steady-State Error Compensation for Reinforcement Learning-Based Control of Power Electronic Systems - Weber, Daniel; Schenke, Maximilian; Wallscheid, Oliver (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Modeling of Masked Droplet Deposition for Site-Controlled Ga Droplets - Feddersen, Stefan; Zolatanosha, Viktoryia; Alshaikh, Ahmed; Reuter, Dirk; Heyn, Christian (Nanomaterials)
Site-controlled Ga droplets on AlGaAs substrates are fabricated using area-selective deposition of Ga through apertures in a mask during molecular beam epitaxy (MBE). The Ga droplets can be crystallized into GaAs quantum dots using a crystallization step under As flux. In order to model the complex process, including the masked deposition of the droplets and a reduction of their number during a thermal annealing step, a multiscale kinetic Monte Carlo (mkMC) simulation of self-assembled Ga droplet formation on AlGaAs is expanded for area-selective deposition. The simulation has only two free model parameters: the activation energy for surface diffusion and the activation energy for thermal escape of adatoms from a droplet. Simulated droplet numbers within the opening of the aperture agree quantitatively with the experimental results down to the perfect site-control, with one droplet per aperture. However, the model parameters are different compared to those of the self-assembled droplet growth. We attribute this to the presence of the mask in close proximity to the surface, which modifies the local process temperature and the As background. This approach also explains the dependence of the model parameters on the size of the aperture.
Keywords: General Materials Science; General Chemical Engineering

UV-enhanced environmental charge compensation in near ambient pressure XPS - Müller, Hendrik; Weinberger, Christian; Grundmeier, Guido; de los Arcos de Pedro, Maria Teresa (Journal of Electron Spectroscopy and Related Phenomena)
Keywords: Physical and Theoretical Chemistry; Spectroscopy; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Radiation; Electronic; Optical and Magnetic Materials

An Experimental and Computational Modeling Study on Additively Manufactured Micro‐Architectured Ti–24Nb–4Zr–8Sn Hollow‐Strut Lattice Structures - Pramanik, Sudipta; Milaege, Dennis; Hein, Maxwell; Andreiev, Anatolii; Schaper, Mirko; Hoyer, Kay-Peter (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

NELLIE: Never-Ending Linking for Linked Open Data - Ahmed, Abdullah Fathi; Sherif, Mohamed Ahmed; Ngomo, Axel-Cyrille Ngonga (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Overcoming the Miscibility Gap of GaN/InN in MBE Growth of Cubic InxGa1–xN - Zscherp, Mario Fabian; Jentsch, Silas Aurel; Müller, Marius Johannes; Lider, Vitalii; Becker, Celina; Chen, Limei; Littmann, Mario; Meier, Falco; Beyer, Andreas; Hofmann, Detlev Michael; As, Donat Josef; Klar, Peter Jens; et al. (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Investigations on the Influences of the Thermomechanical Manufacturing of Aluminium Auxiliary Joining Elements - Borgert, Thomas; Henke, Maximilian; Homberg, Werner (Journal of Manufacturing and Materials Processing)
The demands on joining technology are constantly increasing due to the consistent lightweight construction and the associated increasing material mix. To meet these requirements, the adaptability of the joining processes must be improved to be able to process different material combinations and to react to challenges caused by deviations in the process chain. One example of a highly adaptable process due to the two-step process sequence is thermomechanical joining with Friction Spun Joint Connectors (FSJCs) that can be individually adapted to the joint. In this paper, the potentials of the adaption in the two-stage joining process with aluminium auxiliary joining elements are investigated. To this end, it is first investigated whether a thermomechanical forming process can be used to achieve a uniform and controlled manufacturing regarding the process variable of the temperature as well as the geometry of the FSJC. Based on the successful proof of the high and good repeatability in the FSJC manufacturing, possibilities, and potentials for the targeted influencing of the process and FSJC geometry are shown, based on an extensive variation of the process input variables (delivery condition and thus mechanical properties of the raw parts as well as the process parameters of rotational speed and feed rate). Here it can be shown that above all, the feed rate of the final forming process has the strongest influence on the process and thus also offers the strongest possibilities for influencing it.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Structural transitions during Ni nanoparticle formation by decomposition of a Ni-containing metal-organic framework using in-situ total scattering - Prinz, Nils; Strübbe, Sven; Bauer, Matthias; Zobel, Mirijam (New Journal of Chemistry)
For improved and rational design of catalysts, in-depth knowledge of their formation and structural evolution during synthesis is a key parameter. Thus, preparation of a Ni methanation catalyst derived from...
Keywords: Materials Chemistry; General Chemistry; Catalysis

Quasi-In Situ Localized Corrosion of an Additively Manufactured FeCo Alloy in 5 Wt Pct NaCl Solution - Pramanik, Sudipta; Krüger, Jan Tobias; Schaper, Mirko; Hoyer, Kay-Peter (Metallurgical and Materials Transactions A)
Abstract FeCo alloys are important materials used in pumps and motors in the offshore oil and gas drilling industry. These alloys are subjected to marine environments with a high NaCl concentration, therefore, corrosion and catastrophic failure are anticipated. So, the surface dissolution of additively manufactured FeCo samples is investigated in a quasi- in situ manner, in particular, the pitting corrosion in 5.0 wt pct NaCl solution. The local dissolution of the same sample region is monitored after 24, 72, and 168 hours. Here, the formation of rectangular and circular pits of ultra-fine dimensions (less than 0.5 µ m) is observed with increasing immersion time. In addition, the formation of a corrosion-inhibiting surface layer is detected on the sample surface. Surface dissolution leads to a change in the surface structure, however, no change in grain shape or grain size is noticed. The surface topography after local dissolution is correlated to the grain orientation. Quasi- in situ analysis shows the preferential dissolution of high-angle grain boundaries (HAGBs) leading to a change in the fraction of HAGBs and low-angle grain boundaries fraction (LAGBs). For the FeCo sample, a potentiodynamic polarisation test reveals a corrosion potential (E corr ) of − 0.475 V referred to the standard hydrogen electrode (SHE) and a corrosion exchange current density (i corr ) of 0.0848 A/m 2 . Furthermore, quasi- in situ experiments showed that grains oriented along certain crystallographic directions are corroding more compared to other grains leading to a significant decrease in the local surface height. Grains with a plane normal close to the $$\langle {1}00\rangle$$ ⟨ 100 ⟩ direction reveal lower surface dissolution and higher corrosion resistance, whereas planes normal close to the $$\langle {11}0\rangle$$ ⟨ 110 ⟩ direction and the $$\langle {111}\rangle$$ ⟨ 111 ⟩ direction exhibit a higher surface dissolution.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

Adhesion properties of the hybrid system made of laser-structured aluminium EN AW 6082 and CFRP by co-bonding-pressing process - Wu, Shuang; Delp, Alexander; Freund, Jonathan; Walther, Frank; Haubrich, Jan; Löbbecke, Miriam; Tröster, Thomas (The Journal of Adhesion)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Relationship between laser-generated micro- and nanostructures and the long-term stability of bonded epoxy-aluminum joints - Freund, Jonathan; Löbbecke, Miriam; Delp, Alexander; Walther, Frank; Wu, Shuang; Tröster, Thomas; Haubrich, Jan (The Journal of Adhesion)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Superstructure-dependent stability of DNA origami nanostructures in the presence of chaotropic denaturants - Hanke, Marcel; Dornbusch, Daniel; Tomm, Emilia; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (Nanoscale)
The structural stability of DNA origami nanostructures in various chemical environments is an important factor in numerous applications, ranging from biomedicine and biophysics to analytical chemistry and materials synthesis. In...
Keywords: General Materials Science

Potentials of a friction-induced recycling process to improve resource and energy efficiency in manufacturing technology - Borgert, Thomas; Milaege, Dennis; Schweizer, Swetlana; Homberg, Werner; Schaper, Mirko; Tröster, Thomas (International Journal of Material Forming)
Abstract Efforts to enhance sustainability in all areas of life are increasing worldwide. In the field of manufacturing technology, a wide variety of approaches are being used to improve both resource and energy efficiency. Efficiency as well as sustainability can be improved by creating a circular economy or through energy-efficient recycling processes. As part of the interdisciplinary research group "Light—Efficient—Mobile" investigations on the energy-efficient friction-induced recycling process have been carried out at the department of Forming and Machining Technology at Paderborn University. E.g. using the friction-induced recycling process, different formless solid aluminum materials can be direct recycled into semi-finished products in an energy-efficient manner. The results of investigations with regard to the influence of the geometrical shape and filling rate of the aluminum particles to be recycled as well as the rotational speed of the continuously rotating wheel are explained in this paper. In addition to the recycling of aluminum chips, aluminum particles like powders from the field of additive manufacturing are processed. Based on these results, the future potentials of solid-state recycling processes and their contribution to the circular economy are discussed. The main focus here is on future interdisciplinary research projects to achieve circularity in the manufacturing of user-individual semi-finished products as well as the possibility to selectively adjust the product properties with the continuous recycling process.
Keywords: General Materials Science

Impact of 3D Curvature on the Polarization Orientation in Non-Ising Domain Walls - Acevedo-Salas, Ulises; Croes, Boris; Zhang, Yide; Cregut, Olivier; Dorkenoo, Kokou Dodzi; Kirbus, Benjamin; Singh, Ekta; Beccard, Henrik; Rüsing, Michael; Eng, Lukas M.; Hertel, Riccardo; Eliseev, Eugene A.; et al. (Nano Letters)
Ferroelectric domain boundaries are quasi-two-dimensional functional interfaces with high prospects for nanoelectronic applications. Despite their reduced dimensionality, they can exhibit complex non-Ising polarization configurations and unexpected physical properties. Here, the impact of the three-dimensional (3D) curvature on the polarization profile of nominally uncharged 180° domain walls in LiNbO3 is studied using second-harmonic generation microscopy and 3D polarimetry analysis. Correlations between the domain-wall curvature and the variation of its internal polarization unfold in the form of modulations of the Néel-like character, which we attribute to the flexoelectric effect. While the Néel-like character originates mainly from the tilting of the domain wall, the internal polarization adjusts its orientation due to the synergetic upshot of dipolar and monopolar bound charges and their variation with the 3D curvature. Our results show that curved interfaces in solid crystals may offer a rich playground for tailoring nanoscale polar states.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Vibrational properties of LiNbO3 and LiTaO3 under uniaxial stress - Singh, Ekta; Pionteck, Mike N.; Reitzig, Sven; Lange, Michael; Rüsing, Michael; Eng, Lukas M.; Sanna, Simone (Physical Review Materials)
Structural strain severely impacts material properties, such as the linear and nonlinear optical response. Moreover, strain plays a key role, e.g., in the physics of ferroelectrics and, in particular, of their domain walls. μ-Raman spectroscopy is a well-suited technique for the investigation of such strain effects as it allows to measure the lattice dynamics locally. However, quantifying and reconstructing strain fields from Raman maps requires knowledge on the strain dependence of phonon frequencies. In this paper, we have analyzed both theoretically and experimentally the phonon frequencies in the widely used ferroelectrics lithium niobate and lithium tantalate as a function of uniaxial strain via density functional theory and μ-Raman spectroscopy. Overall, we find a good agreement between our ab initio models and the experimental data performed with a stress cell. The majority of phonons show an increase in frequency under compressive strain, whereas the opposite is observed for tensile strains. Moreover, for E-type phonons, we observe the lifting of degeneracy already at moderate strain fields (i.e., at ±0.2%) along the x and y directions. This paper, hence, allows for the systematic analysis of three-dimensional strains in modern-type bulk and thin-film devices assembled from lithium niobate and tantalate.
Keywords: Physics and Astronomy (miscellaneous); General Materials Science

Thermophoretic Analysis of Biomolecules across the Nanoscales in Self-Assembled Polymeric Matrices - Liu, Ping; Schumann, Nils; Abele, Fabian; Ren, Fazheng; Hanke, Marcel; Xin, Yang; Hartmann, Andreas; Schlierf, Michael; Keller, Adrian; Lin, Weilin; Zhang, Yixin (ACS Applied Nano Materials)
Keywords: General Materials Science

Vibrational Properties of the Potassium Titanyl Phosphate Crystal Family - Neufeld, Sergej; Gerstmann, Uwe; Padberg, Laura; Eigner, Christof; Berth, Gerhard; Silberhorn, Christine; Eng, Lukas M.; Schmidt, Wolf Gero; Rüsing, Michael (Crystals)
The crystal family of potassium titanyl phosphate (KTiOPO4) is a promising material group for applications in quantum and nonlinear optics. The fabrication of low-loss optical waveguides, as well as high-grade periodically poled ferroelectric domain structures, requires a profound understanding of the material properties and crystal structure. In this regard, Raman spectroscopy offers the possibility to study and visualize domain structures, strain, defects, and the local stoichiometry, which are all factors impacting device performance. However, the accurate interpretation of Raman spectra and their changes with respect to extrinsic and intrinsic defects requires a thorough assignment of the Raman modes to their respective crystal features, which to date is only partly conducted based on phenomenological modelling. To address this issue, we calculated the phonon spectra of potassium titanyl phosphate and the related compounds rubidium titanyl phosphate (RbTiOPO4) and potassium titanyl arsenate (KTiOAsO4) based on density functional theory and compared them with experimental data. Overall, this allows us to assign various spectral features to eigenmodes of lattice substructures with improved detail compared to previous assignments. Nevertheless, the analysis also shows that not all features of the spectra can unambigiously be explained yet. A possible explanation might be that defects or long range fields not included in the modeling play a crucial rule for the resulting Raman spectrum. In conclusion, this work provides an improved foundation into the vibrational properties in the KTiOPO4 material family.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Solid solutions of lithium niobate and lithium tantalate: crystal growth and the ferroelectric transition - Bashir, Umar; Böttcher, Klaus; Klimm, Detlef; Ganschow, Steffen; Bernhardt, Felix; Sanna, Simone; Rüsing, Michael; Eng, Lukas M.; Bickermann, Matthias (Ferroelectrics)
Specific heat capacity measurements by differential scanning calorimetry (DSC) of single crystals of solid solutions of LiNbO3 and LiTaO3 are reported and compared with corresponding ab initio calculations, with the aim to investigate the variation of the ferroelectric Curie temperature as a function of composition. For this purpose, single crystals of these solid solutions were grown with Czochralski pulling along the c-axis. Elemental composition of Nb and Ta was investigated using XRF analysis, and small samples with homogeneous and well known composition were used for the DSC measurements. We observed that the ferroelectric Curie temperature decreases linearly with increasing Ta concentration in the LiNb1−x Tax O3 solid solution crystals. Furthermore, the ferroelectric transition width of a mixed crystal appears to be smaller, as compared to pure LiTaO3.
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Increased Sustainability in Fastener Production with the Example of Self-Piercing Rivets - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Journal of Manufacturing and Materials Processing)
The sustainability of the manufacturing industry is of special importance to increase the protection of the environment. The production of fasteners like self-piercing rivets, however, is costly, time-consuming and energy-intensive. The heat treatment and the coating, which are mandatory in conventional self-piercing rivets to achieve adequate strength, ductility and corrosion resistance, are especially crucial in this respect. Within this paper, an approach for an increase in the sustainability in fastener production is presented. The use of alternative, high strain hardening stainless steels as rivet material enables a shortening of the process chain, because post treatment of the rivets after they are formed can be omitted. As the change in rivet material and processing causes some issues along the process chain, the focus of this paper is on the holistic evaluation of the challenges within the forming of high strain hardening steel and the impact of the changed rivet properties on the joining result.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

On the accuracy, stability and computational efficiency of explicit last-stage diagonally implicit Runge–Kutta methods (ELDIRK) for the adaptive solution of phase-field problems - Westermann, Hendrik; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Multiphase elasto-plastic mean-field homogenisation and its consistent linearisation - Lenz, Peter; Kreutzheide, Phil; Mahnken, Rolf (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

Additive Manufacturing and Mechanical Properties of Auxetic and Non-Auxetic Ti24Nb4Zr8Sn Biomedical Stents: A Combined Experimental and Computational Modelling Approach - Pramanik, Sudipta; Milaege, Dennis; Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
The effect of plaque deposition (atherosclerosis) on blood flow behaviour is investigated via computational fluid dynamics and structural mechanics simulations. To mitigate the narrowing of coronary artery atherosclerosis (stenosis), the computational modelling of auxetic and non-auxetic stents was performed in this study to minimise or even avoid these deposition agents in the future. Computational modelling was performed in unrestricted (open) conditions and restricted (in an artery) conditions. Finally, stent designs were produced by additive manufacturing, and mechanical testing of the stents was undertaken. Auxetic stent 1 and auxetic stent 2 exhibit very little foreshortening and radial recoil in unrestricted deployment conditions compared to non-auxetic stent 3. However, stent 2 shows structural instability (strut failure) during unrestricted deployment conditions. For the restricted deployment condition, stent 1 shows a higher radial recoil compared to stent 3. In the tensile test simulations, short elongation for stent 1 due to strut failure is demonstrated, whereas no structural instability is noticed for stent 2 and stent 3 until 0.5 (mm/mm) strain. The as-built samples show a significant thickening of the struts of the stents resulting in short elongations during tensile testing compared to the simulations (stent 2 and stent 3). A modelling framework for the stent deployment system that enables the selection of appropriate stent designs before in vivo testing is required. This leads to the acceleration of the development process and a reduction in time, resulting in less material wastage. The modelling framework shall be useful for doctors designing patient-specific stents.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Heterogeneous Structural Evolution of In–Zn–O Thin Films during Annealing - Moffitt, Stephanie L.; Cao, Chuntian; Van Hest, Maikel F. A. M.; Schelhas, Laura T.; Steinrück, Hans-Georg; Toney, Michael F. (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Anchoring and electro-optic switching of liquid crystals on nano-structured surfaces fabricated by two-photon based nano-printing - Zhang, Bingru; Plidschun, Malte; Schmidt, Markus A.; Kitzerow, Heinz-Siegfried (Optical Materials Express)
The alignment of liquid crystals on surfaces plays a central role in optimizing their performances. In this work, a cutting-edge nano-lithography-based method to control the local orientation of a thermotropic liquid crystal is applied to easily available commercial standard materials and evaluated. Parallel nanogrooves on a substrate, created through 3D nanoprinting in a negative-tone photoresin optimized for two-photon polymerization are used for this purpose. Azimuthal anchoring energies of the order from 10 −6 J/m 2 to 10 −5 J/m 2 are found, depending on the spacing, width and depth of the grooves. In part, these values are larger than those reported previously for another photopolymer. Both uniform alignment and spatial patterns of different alignment directions can be realized. Electro-optic studies confirm the suitability of the method for electrically addressable photonic applications and indicate strong polar anchoring.
Keywords: Electronic; Optical and Magnetic Materials

Luminescent DNA-origami nano-rods dispersed in a lyotropic chromonic liquid crystal - Zhang, Bingru; Nguyen, Linh; Martens, Kevin; Heuer-Jungemann, Amelie; Philipp, Julian; Kempter, Susanne; Rädler, Joachim O.; Liedl, Tim; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Dynamics-induced charge transfer in semiconducting conjugated polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (Journal of Materials Chemistry C)
Dynamics-induced interchain charge transfer in a polymer aggregate in stack configuration can be understood by single-oligomer polaron energy.
Keywords: Materials Chemistry; General Chemistry

Defense-in-Depth als neues Paradigma der sicherheitsgerechten Produktentwicklung: interdisziplinäre, bedrohungsbewusste und lösungsorientierte Security - Gräßler, Iris; Bodden, Eric; Wiechel, Dominik; Pottebaum, Jens (Konstruktion)
inhalt Der verlässliche Betrieb von technischen Produkten wird zunehmend durch bewusste Angriffe bedroht. Vollständige Sicherheit ist dabei nicht möglich, durchschlagende Angriffe sind unvermeidbar (Assume Breach). Dies erfordert einen Paradigmenwechsel in der sicherheitsgerechten Entwicklung mechatronischer und cyber-physischer Systeme hin zu Defense-in-Depth. Systeme müssen so ausgelegt werden, dass sie auch bei gezielten Angriffen möglichst hohe Zuverlässigkeit und Sicherheit gewährleisten. Der hier beschriebene Lösungsansatz erweitert das Systemmodell um Angriffsszenarien und Verteidigungslinien. Diese werden am Beispiel eines industriellen Schließsystems zur Anlagensicherheit erläutert. Entwickler werden sensibilisiert, Angriffe systematisch zu berücksichtigen und interdisziplinär Verteidigungselemente gegenüber Bedrohungen und Angriffen zu spezifizieren.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science; Theoretical Computer Science

Electropolymerization of acrylic acid on steel for enhanced joining by plastic deformation - Duderija, B.; Sahin, F.; Meinderink, D.; Calderón-Gómez, J.C.; Schmidt, H.C.; Homberg, W.; Grundmeier, G.; González-Orive, A. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Dynamics-induced charge transfer in semiconducting conjugated polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (Journal of Materials Chemistry C)
Dynamics-induced interchain charge transfer in a polymer aggregate in stack configuration can be understood by single-oligomer polaron energy.
Keywords: Materials Chemistry; General Chemistry

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Mechanical and Microstructure Characterisation of the Hypoeutectic Cast Aluminium Alloy AlSi10Mg Manufactured by the Twin-Roll Casting Process - Neuser, Moritz; Schaper, Mirko; Grydin, Olexandr (Journal of Manufacturing and Materials Processing)
Multi-material designs (MMD) are more frequently used in the automotive industry. Hereby, the combination of different materials, metal sheets, or cast components, is mechanically joined, often by forming joining processes. The cast components mostly used are high-strength, age-hardenable aluminium alloys of the Al–Si system. Here, the low ductility of the AlSi alloys constitutes a challenge because their brittle nature causes cracks during the joining process. However, by using suitable solidification conditions, it is possible to achieve a microstructure with improved mechanical and joining properties. For this study, we used the twin-roll casting process (TRC) with water-cooled rollers to manufacture the hypoeutectic AlSi10Mg for the first time. Hereby, high solidification rates are realisable, which introduces a microstructure that is about four times finer than in the sand casting process. In particular, it is shown that a fine microstructure close to the modification with Na or Sr is achieved by the high solidification rate in the TRC process without using these elements. Based on this, the mechanical properties increase, and especially the ductility is enhanced. Subsequent joining investigations validate the positive influence of a high solidification rate since cracks in joints can be avoided. Finally, a microstructure-property-joint suitability correlation is presented.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Thermomechanical Joining of Hypoeutectic Aluminium Cast Plates - Borgert, Thomas; Neuser, Moritz; Hoyer, Kay-Peter; Homberg, Werner; Schaper, Mirko (Journal of Manufacturing and Materials Processing)
Consistent lightweight construction in the area of vehicle manufacturing requires the increased use of multi-material combinations. This, in turn, requires an adaptation of standard joining techniques. In multi-material combinations, the importance of integral cast components, in particular, is increasing and poses additional technical challenges for the industry. One approach to solve these challenges is adaptable joining elements manufactured by a thermomechanical forming process. By applying an incremental and thermomechanical joining process, it is possible to react immediately and adapt the joining process inline to reduce the number of different joining elements. In the investigation described in this publication, cast plates made of the cast aluminium alloy EN AC-AlSi9 serve as joining partners, which are processed by sand casting. The joining process of hypoeutectic AlSi alloys is challenging as their brittle character leads to cracks in the joint during conventional mechanical joining. To solve this, the frictional heat of the novel joining process applied can provide a finer microstructure in the hypoeutectic AlSi9 cast alloy. In detail, its Si is finer-grained, resulting in higher ductility of the joint. This study reveals the thermomechanical joining suitability of a hypoeutectic cast aluminium alloy in combination with adaptively manufactured auxiliary joining elements.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Auslegungsmethode zum Kleben höchstfester Stahlwerkstoffe im Landmaschinenbau - Göddecke, Johannes; Göhrs, Tim; Meschut, Gerson; Große Gehling, Manfred (Stahlbau)
Abstract In Konstruktionen des Landmaschinenbaus aus dickeren Blechen (ca. 3–10 mm) findet die Klebtechnik bislang nur wenig Anwendung, obwohl sie in anderen Einsatzgebieten bereits ein etabliertes Fügeverfahren darstellt und viele Vorteile gegenüber anderen Fügeverfahren bietet, da es bisher an Regelwerken bei der Auslegung derartiger Verbindungen fehlt. Ein wesentliches Kriterium bei der Auslegung von Verbindungen im Landmaschinenbau ist die Ermüdungsfestigkeit aufgrund der langen Nutzungsphase der Produkte und der in der Landtechnik vorherrschenden Belastungscharakteristika. Geklebte Verbindungen weisen ein hervorragendes Verhalten bei zyklischer Belastung auf. Die steigenden Anforderungen im Hinblick auf Ressourceneffizienz und Leichtbau führen zu einem Umdenken, da durch den vermehrten Einsatz höherfester Stahlwerkstoffe in Kombination mit der Klebtechnik dieses als umsetzbar erscheint. Ziel ist die Entwicklung einer Methode zur Auslegung geklebter Verbindungen in Konstruktionen mit höherfesten Stahlwerkstoffen in Anlehnung an die FKM‐Richtlinie. Die betriebsrelevanten Beanspruchungen der Landtechnik werden analysiert und an speziellen Probekörpern untersucht. Dabei werden sowohl die mechanischen, thermischen und medialen Einflussfaktoren als auch der Einfluss der Klebfugengeometrie und von Betriebslastenkollektiven untersucht. Die Erkenntnisse werden in einer KMU‐relevanten Vorgehensweise zur Ermittlung von Abminderungsfaktoren zusammengefasst, wodurch die Auslegung der Bauteilfestigkeit sowohl statisch als auch dynamisch möglich ist.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Building and Construction; Civil and Structural Engineering

Measurement, Modelling, and Appli cation of Lubricant Properties at Extreme Pressures - Wingertszahn, Patrick; Schmitt, Sebastian; Thielen, Stefan; Oehler, Manuel; Magyar, Balázs; Koch, Oliver; Hasse, Hans; Stephan, Simon (Tribologie und Schmierungstechnik)
Lubricants play a central role in many technical applications, e.g. in bearings and gears as well as in machining processes. In such applications, lubricants are exposed to extreme conditions in the contact area. In lubrication gaps, the pressure can reach values up to 5 GPa. The thermophysical properties of lubricants, and in particular the viscosity, at such extreme conditions have an important influence on the friction and wear behavior of a tribosystem. Accordingly, reliable lubricant property models are a prerequisite for accurate tribological simulations, e.g. elastohydrodynamic lubrication (EHL) simulations. Presently, the vast majority of experimental thermophysical property data are only available up to 1 GPa. Thus, reliable and robust models with strong extrapolation capabilities to higher pressure are required. In this work, viscosity measurements of squalane in a temperature range be tween 20 °C and 100 °C and pressures up to 1 GPa were carried out. Based on that data, a physical model for the viscosity was developed. The model is built by combining a molecular-based equation of state with the so-called entropy scaling approach. Finally, we demonstrate how this fluid property model can be favorably integrated in an EHL simulation by an application programming interface (API). The novel hybrid modeling approach is promising for future applications.
Keywords: Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanical Engineering; Mechanics of Materials

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.
Keywords: Additive Manufacturing; Laser Sintering; Filled Materials; Composites; Polyamide 613

Antimicrobial Brushes on Titanium via “Grafting to” Using Phosphonic Acid/Pyridinium Containing Block Copolymers - Methling, Rafael; Dückmann, Oliver; Simon, Frank; Wolf‐Brandstetter, Cornelia; Kuckling, Dirk (Macromolecular Materials and Engineering)
Abstract Coating medical implants with antibacterial polymers may prevent postoperative infections which are a common issue for conventional titanium implants and can even lead to implant failure. Easily applicable diblock copolymers are presented that form polymer brushes via “grafting to” mechanism on titanium and equip the modified material with antibacterial properties. The polymers carry quaternized pyridinium units to combat bacteria and phosphonic acid groups which allow the linear chains to be anchored to metal surfaces in a convenient coating process. The polymers are synthesized via reversible‐addition‐fragmentation‐chain‐transfer (RAFT) polymerization and postmodifications and are characterized using NMR spectroscopy and SEC. Low grafting densities are a major drawback of the “grafting to” approach compared to “grafting from”. Thus, the number of phosphonic acid groups in the anchor block are varied to investigate and optimize the surface binding. Modified titanium surfaces are examined regarding their composition, wetting behavior, streaming potential, and coating stability. Evaluation of the antimicrobial properties revealed reduced bacterial adhesion and biofilm formation for certain polymers, albeit the cell biocompatibility against human gingival fibroblasts is also impaired. The presented findings show the potential of easy‐to‐apply polymer coatings and aid in designing next‐generation implant surface modifications.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; General Chemical Engineering

Spectral and Energy Efficiency Maximization of MISO STAR-RIS-Assisted URLLC Systems - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard A. (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Nonlinear Dielectric Geometric-Phase Metasurface with Simultaneous Structure and Lattice Symmetry Design - Liu, Bingyi; Geromel, René; Su, Zhaoxian; Guo, Kai; Wang, Yongtian; Guo, Zhongyi; Huang, Lingling; Zentgraf, Thomas (ACS Photonics)
In this work, we utilize thin dielectric meta-atoms placed on a silver substrate to efficiently enhance and manipulate the third-harmonic generation. We theoretically and experimentally reveal that when the structural symmetry of the meta-atom is incompatible with the lattice symmetry of an array, some generalized nonlinear geometric phases appear, which offers new possibilities for harmonic generation control beyond the accessible symmetries governed by the selection rule. The underlying mechanism is attributed to the modified rotation of the effective principal axis of a dense meta-atom array, where the strong coupling among the units gives rise to a generalized linear geometric phase modulation of the pump light. Therefore, nonlinear geometric phases carried by third-harmonic emissions are the natural result of the wave-mixing process among the modes excited at the fundamental frequency. This mechanism further points out a new strategy to predict the nonlinear geometric phases delivered by the nanostructures according to their linear responses. Our design is simple and efficient and offers alternatives for the nonlinear meta-devices that are capable of flexible photon generation and manipulation.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

Influence of thermomechanical processing on the microstructural and mechanical properties of steel 22MnB5 - Reitz, A.; Grydin, O.; Schaper, M. (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Second Harmonic Optical Circular Dichroism of Plasmonic Chiral Helicoid-III Nanoparticles - Spreyer, Florian; Mun, Jungho; Kim, Hyeohn; Kim, Ryeong Myeong; Nam, Ki Tae; Rho, Junsuk; Zentgraf, Thomas (ACS Photonics)
While plasmonic particles can provide optical resonances in a wide spectral range from the lower visible up to the near-infrared, often, symmetry effects are utilized to obtain particular optical responses. By breaking certain spatial symmetries, chiral structures arise and provide robust chiroptical responses to these plasmonic resonances. Here, we observe strong chiroptical responses in the linear and nonlinear optical regime for chiral L-handed helicoid-III nanoparticles and quantify them by means of an asymmetric factor, the so-called g-factor. We calculate the linear optical g-factors for two distinct chiroptical resonances to −0.12 and –0.43 and the nonlinear optical g-factors to −1.45 and −1.63. The results demonstrate that the chirality of the helicoid-III nanoparticles is strongly enhanced in the nonlinear regime.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay S.; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg K. N. (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Conformal Pressure and Fast-Charging Li-Ion Batteries - Cao, Chuntian; Steinrück, Hans-Georg; Paul, Partha P; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew; Kasse, Robert M; Thampy, Vivek; Yusuf, Maha; Nelson Weker, Johanna; Shyam, Badri; Subbaraman, Ram; et al. (Journal of The Electrochemical Society)
Abstract Batteries capable of extreme fast-charging (XFC) are a necessity for the deployment of electric vehicles. Material properties of electrodes and electrolytes along with cell parameters such as stack pressure and temperature have coupled, synergistic, and sometimes deleterious effects on fast-charging performance. We develop a new experimental testbed that allows precise and conformal application of electrode stack pressure. We focus on cell capacity degradation using single-layer pouch cells with graphite anodes, LiNi0.5Mn0.3Co0.2O2 (NMC532) cathodes, and carbonate-based electrolyte. In the tested range (10 – 125 psi), cells cycled at higher pressure show higher capacity and less capacity fading. Additionally, Li plating decreases with increasing pressure as observed with scanning electron microscopy (SEM) and optical imaging. While the loss of Li inventory from Li plating is the largest contributor to capacity fade, electrochemical and SEM examination of the NMC cathodes after XFC experiments show increased secondary particle damage at lower pressure. We infer that the better performance at higher pressure is due to more homogenous reactions of active materials across the electrode and less polarization through the electrode thickness. Our study emphasizes the importance of electrode stack pressure in XFC batteries and highlights its subtle role in cell conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Corrosion fatigue behavior of electron beam melted iron in simulated body fluid - Wackenrohr, Steffen; Torrent, Christof Johannes Jaime; Herbst, Sebastian; Nürnberger, Florian; Krooss, Philipp; Ebbert, Christoph; Voigt, Markus; Grundmeier, Guido; Niendorf, Thomas; Maier, Hans Jürgen (npj Materials Degradation)
Abstract Pure iron is very attractive as a biodegradable implant material due to its high biocompatibility. In combination with additive manufacturing, which facilitates great flexibility of the implant design, it is possible to selectively adjust the microstructure of the material in the process, thereby control the corrosion and fatigue behavior. In the present study, conventional hot-rolled (HR) pure iron is compared to pure iron manufactured by electron beam melting (EBM). The microstructure, the corrosion behavior and the fatigue properties were studied comprehensively. The investigated sample conditions showed significant differences in the microstructures that led to changes in corrosion and fatigue properties. The EBM iron showed significantly lower fatigue strength compared to the HR iron. These different fatigue responses were observed under purely mechanical loading as well as with superimposed corrosion influence and are summarized in a model that describes the underlying failure mechanisms.
Keywords: Materials Chemistry; Materials Science (miscellaneous); Chemistry (miscellaneous); Ceramics and Composites

Efficient Frequency Conversion with Geometric Phase Control in Optical Metasurfaces - Reineke Matsudo, Bernhard; Sain, Basudeb; Carletti, Luca; Zhang, Xue; Gao, Wenlong; Angelis, Costantino; Huang, Lingling; Zentgraf, Thomas (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Consideration of the manufacturing history of sheet metal components for the adaptation of a clinching process - Heyser, Per; Wiesenmayer, S; Frey, P; Nehls, T; Scharr, C; Flügge, W; Merklein, M; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
The process chain for the manufacturing of sheet metal components in mass production includes various cutting and forming operations, which influence the resulting properties of the parts and therefore subsequent manufacturing steps, such as clamping and joining. It is shown that clamping of the components leads to superimposed residual stresses and geometry changes. Therefore, the part properties differ from the initial state of the semifinished products, which has to be considered in the design of clinched joints. This paper presents an approach for coupled determination of the properties of semifinished and finished parts during deep drawing and clamping as well as their effects on the joint quality during clinching. One method for the effective and efficient determination of the properties of semifinished products and components during production is using process data from the preceding manufacturing processes, which is concretely presented in this work. In addition to the interconnection of the entire production chain, it is necessary to define relevant process data for each individual manufacturing step and to correlate the data with the material properties reliably. Therefore, the cross-process interactions of different steps of the process chain for the manufacturing of sheet metal components and the effect of process variations on subsequent manufacturing steps are investigated. Consequently, the boundary conditions for a mechanical joining process based on data from preceding process steps can be predicted.
Keywords: Mechanical Engineering; General Materials Science

Environment‐Dependent Stability and Mechanical Properties of DNA Origami Six‐Helix Bundles with Different Crossover Spacings - Xin, Yang; Piskunen, Petteri; Suma, Antonio; Li, Changyong; Ijäs, Heini; Ojasalo, Sofia; Seitz, Iris; Kostiainen, Mauri A.; Grundmeier, Guido; Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Remote epitaxy of InxGa1-xAs (0 0 1) on graphene covered GaAs(0 0 1) substrates - Henksmeier, T.; Schulz, J.F.; Kluth, E.; Feneberg, M.; Goldhahn, R.; Sanchez, A.M.; Voigt, M.; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Influence of hydrogel coatings on corrosion and fatigue of iron in simulated body fluid - Huang, Jingyuan; Voigt, Markus; Wackenrohr, Steffen; Ebbert, Christoph; Keller, Adrian; Maier, Hans Jürgen; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Effect of Surface Hydrophobicity on the Adsorption of a Pilus-Derived Adhesin-like Peptide - Yang, Yu; Huang, Jingyuan; Dornbusch, Daniel; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian; Cheung, David L. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Multimodal quantification of degradation pathways during extreme fast charging of lithium-ion batteries - McShane, Eric J.; Paul, Partha P.; Tanim, Tanvir R.; Cao, Chuntian; Steinrück, Hans-Georg; Thampy, Vivek; Trask, Stephen E.; Dunlop, Alison R.; Jansen, Andrew N.; Dufek, Eric J.; Toney, Michael F.; Weker, Johanna Nelson; et al. (Journal of Materials Chemistry A)
Using a unique combination of advanced characterization techniques, we identify specific degradation mechanisms and quantify degradative species formed during fast charge cycling of lithium-ion battery pouch cells.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Simultaneous neutron and X-ray tomography for visualization of graphite electrode degradation in fast-charged lithium-ion batteries - Yusuf, Maha; LaManna, Jacob M.; Paul, Partha P.; Agyeman-Budu, David N.; Cao, Chuntian; Dunlop, Alison R.; Jansen, Andrew N.; Polzin, Bryant J.; Trask, Stephen E.; Tanim, Tanvir R.; Dufek, Eric J.; Thampy, Vivek; et al. (Cell Reports Physical Science)
Keywords: General Physics and Astronomy; General Energy; General Engineering; General Materials Science; General Chemistry

Asymmetric parametric generation of images with nonlinear dielectric metasurfaces - Kruk, Sergey S.; Wang, Lei; Sain, Basudeb; Dong, Zhaogang; Yang, Joel; Zentgraf, Thomas; Kivshar, Yuri (Nature Photonics)
Subwavelength dielectric resonators assembled into metasurfaces have become a versatile tool for miniaturizing optical components approaching the nanoscale. An important class of metasurface functionalities is associated with asymmetry in both the generation and transmission of light with respect to reversals of the positions of emitters and receivers. The nonlinear light–matter interaction in metasurfaces offers a promising pathway towards miniaturization of the asymmetric control of light. Here we demonstrate asymmetric parametric generation of light in nonlinear metasurfaces. We assemble dissimilar nonlinear dielectric resonators into translucent metasurfaces that produce images in the visible spectral range on being illuminated by infrared radiation. By design, the metasurfaces produce different and completely independent images for the reversed direction of illumination, that is, when the positions of the infrared emitter and the visible light receiver are exchanged. Nonlinearity-enabled asymmetric control of light by subwavelength resonators paves the way towards novel nanophotonic components via dense integration of large quantities of nonlinear resonators into compact metasurface designs.
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science

Investigation of the influence of formed, non-rotationally symmetrical pin geometries and their effect on the joint quality of steel and aluminium sheets by direct pin pressing - Römisch, David; Kraus, Martin; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Resource-saving and sustainable production is becoming increasingly important regarding social, political and economic aspects, thus making the use of lightweight-construction technologies a current trend. For this reason, multi-material-systems made of high-strength steel and aluminium as well as metal and fibre-reinforced plastics gain in importance. However, different material properties, e.g. stiffness, thermal expansion coefficients or chemical incompatibilities, are challenging for conventional joining technologies. Joining by cold formed pin structures has shown to have high potential for joining multi-material-systems. These pins can be joined either by direct pin pressing into an unperforated joining partner or by caulking, where the pins are inserted through a pre-punched joining partner and the pin head is upset, resulting in a form-fit joint. Usually, cylindrical pins are used for joining. However, non-rotationally symmetrical pin geometries offer the possibility of introducing a predetermined breaking point or reinforcing a connection in the principal force direction. In this work, cylindrical pins as well as non-rotationally symmetrical pin geometries, such as polygonal and oval pin structures, are cold extruded from the sheet metal plane of an HCT590X+Z dual phase steel and joined in the next step with an EN AW-6014 aluminium using direct pin pressing. Since the formation of an undercut has an crucial influence on the joint strength, the investigations will be focused on the resulting joint geometry. In addition, the effect of different pin heights will be examined to analyse the joint formation at different levels of compression of the pin structures. Finally, the joints are evaluated regarding their joint strength in tensile shear tests and cross tension tests. Here the flow resistance of the geometry used as well as the pin height and thus the strain hardening of the pin base during the extrusion of the pins play a decisive role for the shear strength.
Keywords: Mechanical Engineering; General Materials Science

Joining of CFRT/Steel Hybrid Parts via Direct Pressing of Cold Formed Non-Rotational Symmetric Pin Structures - Popp, Julian; Römisch, David; Merklein, Marion; Drummer, Dietmar (Applied Sciences)
In this study, quasi-unidirectional continuous fiber reinforced thermoplastics (CFRTs) are joined with metal sheets via cold formed cylindrical, elliptical and polygonal pin structures which are directly pressed into the CFRT component after local infrared heating. In comparison to already available studies, the unique novelty is the use of non-rotational symmetric pin structures for the CFRT/metal hybrid joining. Thus, a variation in the fiber orientation in the CFRT component as well as a variation in the non-rotational symmetric pins’ orientation in relation to the sample orientation is conducted. The created samples are consequently mechanically tested via single lap shear experiments in a quasi-static state. Finally, the failure behavior of the single lap shear samples is investigated with the help of microscopic images and detailed photographs. In the single lap shear tests, it could be shown that non-rotational symmetric pin structures lead to an increase in maximum testing forces of up to 74% when compared to cylindrical pins. However, when normalized to the pin foot print related joint strength, only one polygonal pin variation showed increased joint strength in comparison to cylindrical pin structures. The investigation of the failure behavior showed two distinct failure modes. The first failure mode was failure of the CFRT component due to an exceedance of the maximum bearing strength of the pin-hole leading to significant damage in the CFRT component. The second failure mode was pin-deflection due to the applied testing load and a subsequent pin extraction from the CFRT component resulting in significantly less visible damage in the CFRT component. Generally, CFRT failure is more likely with a fiber orientation of 0° in relation to the load direction while pin extraction typically occurs with a fiber orientation of 90°. It is assumed that for future investigations, pin structures with an undercutting shape that creates an interlocking joint could counteract the tendency for pin-extraction and consequently lead to increased maximum joint strengths.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Enhanced corrosion resistance of epoxy-films on ultra-thin SiOx PECVD film coated laser surface melted Al-alloys - Varghese, J.; Vieth, P.; Xie, X.; Grundmeier, Guido (SN Applied Sciences)
Abstract The influence of ultra-thin SiO x plasma deposited films on the corrosion resistance of adhesive films on a laser surface melted 7075 aluminium alloy was investigated by means of complementary techniques in comparison to the just laser surface melted state. Laser surface melting (LSM) was performed using a continuous wave mode at a wavelength of 1064 nm. Ultra-thin plasma polymer films were deposited from a mixture of hexamethyldisilane (HMDSO), oxygen, and argon by means of an audio-frequency glow discharge. The surface morphology and surface chemistry compositions were investigated by employing field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy (EDX), diffuse reflection infrared Fourier transform spectroscopy, and X-ray photoelectron spectroscopy. The corrosion resistance of plasma polymer coated LSM Al-7075 alloy was studied using linear sweep voltammetry and electrochemical impedance spectroscopy in a chloride-containing electrolyte. The electrochemical studies showed an improved corrosion resistance for plasma film-coated alloys compared to the just laser surface melted state. To study the corresponding surface adhesive properties, the samples were coated with an epoxy amine adhesive. 90°-peel test under humid conditions confirmed the improvement of interfacial wet-adhesion corrosion tests showed a strong improvement of the delamination resistance of adhesives caused by the ultra-thin interfacial SiO x -films.
Keywords: General Earth and Planetary Sciences; General Physics and Astronomy; General Engineering; General Environmental Science; General Materials Science; General Chemical Engineering

Combined in-situ attenuated total reflection-Fourier transform infrared spectroscopy and single molecule force studies of poly(acrylic acid) at electrolyte/oxide interfaces at acidic pH - Neßlinger, Vanessa; Orive, Alejandro G.; Meinderink, Dennis; Grundmeier, Guido (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Low Areal Densities of InAs Quantum Dots on GaAs(100) Prepared by Molecular Beam Epitaxy - Verma, A.K.; Bopp, F.; Finley, J.J.; Jonas, B.; Zrenner, A.; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Combined Effects of Uniform Applied Pressure and Electrolyte Additives in Lithium-Metal Batteries - Kasse, Robert M.; Geise, Natalie R.; Sebti, Elias; Lim, Kipil; Takacs, Christopher J.; Cao, Chuntian; Steinrück, Hans-Georg; Toney, Michael F. (ACS Applied Energy Materials)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Electrochemistry; Energy Engineering and Power Technology; Chemical Engineering (miscellaneous)

In-Mold-Assembly of Hybrid Bending Structures by Compression Molding - Stallmeister, Tim; Tröster, Thomas (Key Engineering Materials)
The further development of in-mold-assembly (IMA) technologies for structural hybrid components is of great importance for increasing the economic efficiency and thus the application potential. This paper presents an innovative IMA process concept for the manufacturing of bending loaded hybrid components consisting of two outer metal belts and an inner core structure made of glass mat reinforced thermoplastic (GMT). In this process, the core structure, which is provided with stiffening ribs and functional elements, is formed and joined to two metal belts in one single step. For experimental validation of the concept, the development of a prototypic molding tool and the manufacturing of hybrid beams including process parameters are described. Three-point bending tests and optical measurement technologies are used to characterize the failure behavior and mechanical properties of the produced hybrid beams. It was found that the innovative IMA process enables the manufacturing of hybrid components with high energy absorption and low weight in one step. The mass-specific energy absorption is increased by 693 % compared to pure GMT beams.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Direct visualization of the drug loading of single DNA origami nanostructures by AFM-IR nanospectroscopy - Hanke, Marcel; Grundmeier, Guido; Keller, Adrian (Nanoscale)
The efficient loading of DNA nanostructures with intercalating or groove-binding drugs is an important prerequisite for various applications in drug delivery. However, unambiguous verification and quantification of successful drug loading...
Keywords: General Materials Science

A comparison of heuristic, statistical, and machine learning methods for heated tool butt welding of two different materials - Gevers, Karina; Tornede, Alexander; Wever, Marcel Dominik; Schöppner, Volker; Hüllermeier, Eyke (Welding in the World)
Abstract Heated tool butt welding is a method often used for joining thermoplastics, especially when the components are made out of different materials. The quality of the connection between the components crucially depends on a suitable choice of the parameters of the welding process, such as heating time, temperature, and the precise way how the parts are then welded. Moreover, when different materials are to be joined, the parameter values need to be tailored to the specifics of the respective material. To this end, in this paper, three approaches to tailor the parameter values to optimize the quality of the connection are compared: a heuristic by Potente, statistical experimental design, and Bayesian optimization. With the suitability for practice in mind, a series of experiments are carried out with these approaches, and their capabilities of proposing well-performing parameter values are investigated. As a result, Bayesian optimization is found to yield peak performance, but the costs for optimization are substantial. In contrast, the Potente heuristic does not require any experimentation and recommends parameter values with competitive quality.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Quantum Dot Molecule Devices with Optical Control of Charge Status and Electronic Control of Coupling - Bopp, Frederik; Rojas, Jonathan; Revenga, Natalia; Riedl, Hubert; Sbresny, Friedrich; Boos, Katarina; Simmet, Tobias; Ahmadi, Arash; Gershoni, David; Kasprzak, Jacek; Ludwig, Arne; Reitzenstein, Stephan; et al. (Advanced Quantum Technologies)
Keywords: Electrical and Electronic Engineering; Computational Theory and Mathematics; Condensed Matter Physics; Mathematical Physics; Nuclear and High Energy Physics; Electronic; Optical and Magnetic Materials; Statistical and Nonlinear Physics

Electronic Structures of Group III–V Element Haeckelite Compounds: A Novel Family of Semiconductors, Dirac Semimetals, and Topological Insulators - Khazaei, Mohammad; Ranjbar, Ahmad; Kang, Yoon‐Gu; Liang, Yunye; Khaledialidusti, Rasoul; Bae, Soungmin; Raebiger, Hannes; Wang, Vei; Han, Myung Joon; Mizoguchi, Hiroshi; Bahramy, Mohammad S.; Kühne, Thomas; et al. (Advanced Functional Materials)
Keywords: Electrochemistry; Condensed Matter Physics; Biomaterials; Electronic; Optical and Magnetic Materials

Real-Space Identification of Non-Noble Single Atomic Catalytic Sites within Metal-Coordinated Supramolecular Networks - Schulze Lammers, Bertram; López-Salas, Nieves; Stein Siena, Julya; Mirhosseini, Hossein; Yesilpinar, Damla; Heske, Julian Joachim; Kühne, Thomas; Fuchs, Harald; Antonietti, Markus; Mönig, Harry (ACS Nano)
Keywords: General Physics and Astronomy; General Engineering; General Materials Science

Surface Passivation and Detrimental Heat-Induced Diffusion Effects in RbF-Treated Cu(In,Ga)Se2 Solar Cell Absorbers - Elizabeth, Amala; Sahoo, Sudhir K.; Phirke, Himanshu; Kodalle, Tim; Kühne, Thomas; Audinot, Jean-Nicolas; Wirtz, Tom; Redinger, Alex; Kaufmann, Christian A.; Mirhosseini, Hossein; Mönig, Harry (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Fingerprints Indicating Superior Properties of Internal Interfaces in Cu(In,Ga)Se 2 Thin‐Film Solar Cells - Raghuwanshi, Mohit; Chugh, Manjusha; Sozzi, Giovanna; Kanevce, Ana; Kühne, Thomas; Mirhosseini, Hossein; Wuerz, Roland; Cojocaru‐Mirédin, Oana (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Do Lead Halide Hybrid Perovskites Have Hydrogen Bonds? - Ibaceta-Jaña, Josefa; Chugh, Manjusha; Novikov, Alexander S.; Mirhosseini, Hossein; Kühne, Thomas; Szyszka, Bernd; Wagner, Markus R.; Muydinov, Ruslan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian Joachim; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas; Antonietti, Markus; López-Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

Giant Orbital Anisotropy with Strong Spin–Orbit Coupling Established at the Pseudomorphic Interface of the Co/Pd Superlattice - Kim, Sanghoon; Pathak, Sachin; Rhim, Sonny H.; Cha, Jongin; Jekal, Soyoung; Hong, Soon Cheol; Lee, Hyun Hwi; Park, Sung‐Hun; Lee, Han‐Koo; Park, Jae‐Hoon; Lee, Soogil; Steinrück, Hans-Georg; et al. (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)